Peter Joachim Friedrich – 85 (3.03.1938) - Raudjärv, Matti (Estonian Discussions on Economic Policy, 2024)
Active participant in the conference (from 2006 to 2014 and 2017 – 2018) and a member of the editorial board of the international scientific journal Estonian Discussions on Economic Policy in three languages and author/co-author of many articles in the journal, professor emeritus of the University of the Bundeswehr Munich (Federal Republic of Germany) (and later visiting professor and senior researcher of the University of Tartu) Dr Peter Joachim Friedrich had his 85th birthday (on 03.03.2023). We wish our productive and hard-working colleague good health, success and happiness in his future activities.